2016
DOI: 10.1007/s10974-016-9447-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effects of tropomyosin mutations on its flexibility and interactions with filamentous actin using molecular dynamics simulation

Abstract: Tropomyosin (Tpm) is a two-chained α-helical coiled-coil protein that binds to filamentous actin (F-actin), and regulates its interactions with myosin by occupying three average positions on F-actin (blocked, closed, and open). Mutations in the Tpm are linked to heart diseases including hypertrophic cardiomyopathy (HCM) and dilated cardiomyopathy (DCM). To elucidate the molecular mechanisms of Tpm mutations (including DCM mutation E54K, HCM mutations E62Q, A63V, K70T, V95A, D175N, E180G, L185R, E192K, and a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 100 publications
5
35
0
1
Order By: Relevance
“…Among Tm noncanonical amino acids, recent studies have examined two highly conserved residues in the middle part of the aaTm molecule: D137 (a charged residue in a d hydrophobic position) and G126 (a small, neutral residue in a g charged position). Replacement of these residues with canonical ones, D137L and G126R (9,10), was shown in solution studies to significantly increase coiled-coil stability and decrease molecular mobility or flexibility (9,(11)(12)(13). A significant decrease in the flexibility of reconstructed thin filaments with the combined D137L/G126R substitution was also shown by means of the two-bead optical trap technique (14).…”
Section: Introductionmentioning
confidence: 90%
“…Among Tm noncanonical amino acids, recent studies have examined two highly conserved residues in the middle part of the aaTm molecule: D137 (a charged residue in a d hydrophobic position) and G126 (a small, neutral residue in a g charged position). Replacement of these residues with canonical ones, D137L and G126R (9,10), was shown in solution studies to significantly increase coiled-coil stability and decrease molecular mobility or flexibility (9,(11)(12)(13). A significant decrease in the flexibility of reconstructed thin filaments with the combined D137L/G126R substitution was also shown by means of the two-bead optical trap technique (14).…”
Section: Introductionmentioning
confidence: 90%
“…A 2012 study used MD to study familial HCM associated Tm mutations D175N and E180G and found that both mutations lead to increased flexibility of Tm and therefore, decreased persistence length of the molecule (Li et al, 2012). Another MD study has also been performed on HCM Tm mutations E62Q, A63V, K70T, V95A, D175N, E180G, L185R, E192K in order to explore the effects of point mutations on Tm flexibility and Tm-actin interactions (Zheng et al, 2016). In the case of DCM, a time-independent electrostatic snapshot of the DCM associated Tm mutation showed that E54K and E40K mutations alter the surface charge of Tm, which may affect Tm-actin interaction (Olson et al, 2001; Chang et al, 2014).…”
Section: Insights and Challenges From Molecular Modeling Of Regulatormentioning
confidence: 99%
“…In the case of DCM, a time-independent electrostatic snapshot of the DCM associated Tm mutation showed that E54K and E40K mutations alter the surface charge of Tm, which may affect Tm-actin interaction (Olson et al, 2001; Chang et al, 2014). A time-dependent MD study was also performed on the E54K Tm mutant in combination with 7 actin monomers and showed that this mutation causes increased stiffness and decreased curvature in the Tm molecule overall while stabilizing and destabilizing the coiled coil structure in different regions of the molecule and greatly weakening Tm-actin binding (Zheng et al, 2016). More MD studies are needed in the area of Tm DCM mutations in order to visualize effects of other mutations, such as E40K, that may affect Tm-actin and Tm-cTn interactions.…”
Section: Insights and Challenges From Molecular Modeling Of Regulatormentioning
confidence: 99%
“…However, recent work has shown that point mutations in tropomyosin can also affect the energy landscape of tropomyosin interactions with actin, providing another potential route for mutations to affect thin filament calcium regulation (Orzechowski et al, 2014a,b). Altered actin binding by mutant tropomyosin is also supported by numerous experimental and computational studies (Boussouf et al, 2007; Janco et al, 2012; Zheng et al, 2016). The surface interactions of tropomyosin and actin may ultimately affect myosin crossbridge formation, as suggested by length perturbation analysis studies (Bai et al, 2011).…”
Section: Introductionmentioning
confidence: 76%
“…This suggests that mutation effects are not confined to stiffness alone and that other molecular mechanisms should be considered. Indeed, tropomyosin mutants have previously been determined to alter the interactions between tropomyosin and the actin surface (Orzechowski et al, 2014a; Zheng et al, 2016), which may in turn affect both the blocked-to-closed and closed-to-open (myosin-induced) transitions of tropomyosin across actin. We therefore entertained the possibility that introducing changes to the BC equilibrium constant and duty cycle in addition to the assumed stiffness changes could produce a reasonable fit to mutant data.…”
Section: Resultsmentioning
confidence: 99%